2020
DOI: 10.1089/acm.2019.0165
|View full text |Cite
|
Sign up to set email alerts
|

Does the Application of Tecar Therapy Affect Temperature and Perfusion of Skin and Muscle Microcirculation? A Pilot Feasibility Study on Healthy Subjects

Abstract: Background: Tecar therapy (TT) is an endogenous thermotherapy used to generate warming up of superficial and deep tissues. TT capability to affect the blood flow is commonly considered to be the primary mechanism to promote tissue healing processes. Despite some preliminary evidence about its clinical efficacy, knowledge on the physiologic responses induced by TT is lacking. Objective: The aim of this quantitative randomized pilot study was to determinate if TT, delivered in two modes (resistive and capacitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 22 publications
0
41
0
2
Order By: Relevance
“…For better understanding of the temperature changes and electric current flow in conditions similar to rehabilitation treatments, we adapted a power threshold similar to that normally used during treatments on real patients with the T-Plus model [7,18] but without the possibility of receiving patient's feedback. This is based on the power level that the therapist can easily identify and control during the therapy, and the watts (absorbed power) that the device samples during application.…”
Section: Interventionmentioning
confidence: 99%
“…For better understanding of the temperature changes and electric current flow in conditions similar to rehabilitation treatments, we adapted a power threshold similar to that normally used during treatments on real patients with the T-Plus model [7,18] but without the possibility of receiving patient's feedback. This is based on the power level that the therapist can easily identify and control during the therapy, and the watts (absorbed power) that the device samples during application.…”
Section: Interventionmentioning
confidence: 99%
“…Capacitive mode is provided with an insulating ceramic layer and the energetic transmission generates heat in superficial tissue layers, with a selective action in tissues with low-impedance (water rich). Resistive mode has no insulating ceramic layer, the radiofrequency energy passes directly through the body in the direction of the inactive electrode, generating heat in the deeper and more resistant tissues (with less water content) [17].…”
Section: Introductionmentioning
confidence: 99%
“…The resistive mode (RET) targets denser tissues containing more fat and fiber (such as bones, ligaments and tendons). High frequency waves penetrate deep into tissues and increase both exchanges and temperature and a recent study has demonstrated the effects of RF on the skin microcirculation and the intramuscular blood flow [19,20]. This has been shown to increase vascularization and reduce inflammation and swelling and to accelerate the healing process and provide pain relief [12].…”
Section: Introductionmentioning
confidence: 99%